Electrochemical Properties of CMC–PVA Polymer Blend Electrolyte for Solid State Electric Double Layer Capacitors - M. A., Saadiah; M.Z., Kufian; I. I., Misnon; A. S., Samsudin (Springer, 2021)
In this work, the electrochemical properties of polymer blend electrolyte (PBE) based CMC-PVA is presented for electrical double layer capacitance (EDLC) application. CMC-PVA PBE is incorporated in two different systems which contain an (1) ammonium nitrate (NH4NO3) ionic dopant (System I), and (2) ethylene carbonate (EC) plasticizer (System II). The ionic conductivity of PBE based on CMC (55 wt.%)–PVA (15 wt.%)–NH4NO3 (30 wt.%) and CMC (53 wt.%)–PVA (13 wt.%)–NH4NO3 (28 wt.%)–EC (6 wt.%) were optimized at room temperature with value of 1.70 × 10−3 S/cm and 3.92 × 10−3 S/cm, respectively. The ionic conduction for both systems shows Arrhenius behavior when tested at different temperatures. Electrochemical properties of the fabricated EDLC cell were analyzed for their electrochemical properties and System II showed higher specific capacitance than System I with values of 64.9 F/g and 89.1 F/g, respectively, based on a CV scan rate of 2 mV/s. Both fabricated EDLC show outstanding cycling stability over 10,000 cycles, which indicates that the present PBE based CMC–PVA has outstanding electrochemical performance and is a promising candidate for EDLC application.